Pengaruh Debt to Equity Ratio dan Current Ratio terhadap Return on Equity pada Subsektor Perbankan BUKU IV yang Terdaftar di BEI Tahun 2022–2025 - Najwa Az Zahra; Suryanto Sosrowidigdo; Siti Nurjanah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
The post-pandemic trajectory of profitability among Indonesia's BUKU IV banking institutions has prompted renewed attention toward the extent to which financial fundamentals contribute to corporate performance. Inconsistencies reported in prior empirical findings regarding the effects of the Debt-to-Equity Ratio (DER) and Current Ratio (CR) on Return on Equity (ROE) indicate that these relationships remain open to further investigation. Employing a quantitative approach, this study examines BUKU IV banks listed on the Indonesia Stock Exchange over the 2022–2025 period by utilizing annual financial statement data obtained through purposive sampling techniques. The estimation results derived from multiple linear regression suggest that higher leverage, as reflected by DER, is associated with an increase in ROE, whereas greater liquidity represented by CR corresponds to a decline in profitability. The simultaneous influence of both indicators on ROE is statistically significant, accounting for 41.6% of the observed variation in profitability, while the unexplained proportion may be attributable to other determinants not incorporated within the analytical framework of this study.